The analysis of Higher-Order Thinking skills in English reading comprehension tests in Malaysia - Randip Kaur Valdev Singh,; Azianura Hani Shaari, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The current English language education in Malaysia has integrated the Higher-Order Thinking Skills (HOTS) as part of its testing and evaluation system, which aims to enhance students’ cognitive skills and abilities in learning. Having a higher-order thinking ability at the earliest stage of formal education (primary and elementary levels) is essential in order to meet the growing demand for highly intelligent and professional workers in the future. The present study aims to identify the use of HOTS items in selected English reading comprehension examinations for Standard 6 students in Malaysia. 80 reading comprehension items were selected from various final examination papers distributed in eight different states in the country. Data were quantitatively analysed using content analysis based on the levels of cognitive listed in Bloom’s Taxonomy. Apart from that, the data were also analysed based on a series of professional evaluations made by four content experts in the country. The findings indicate that most reading comprehension questions in the English examination papers need further revisions in order to achieve the standard of HOTS that have become part of the new curriculum and national education policy. Based on the findings, some practical suggestions have also been developed to further enhance the use of HOTS in English teaching and learning practices in Malaysia.